2014
DOI: 10.4028/www.scientific.net/kem.611-612.76
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Hot Deformation Behavior of an Al-Mg-Sc-Zr Alloy under Plane Strain Condition

Abstract: This study investigates the hot deformation behavior of a new Al-Mg-Sc-Zr alloy under plane strain conditions. Flow curves corrected for deformation heating were calculated for strain rates between 0.01 and 10s-1 in a temperature range of 200 to 400°C. To evaluate the deformation behavior, strain rate sensitivity as well as flow localization parameter maps were calculated for strains of 0.2, 0.4, and 0.6. In addition, microstructural investigations and hardness measurements were performed for selected samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In addition, we showed that precipitates influenced the materials behavior during hot deformation [12]. Based on the outcome of the fundamental investigations mentioned above, the present study shows more practical aspects of the complex interactions occurring during processing of the given AlMg4Sc0.4Zr0.12 alloy.…”
Section: Methodssupporting
confidence: 60%
“…In addition, we showed that precipitates influenced the materials behavior during hot deformation [12]. Based on the outcome of the fundamental investigations mentioned above, the present study shows more practical aspects of the complex interactions occurring during processing of the given AlMg4Sc0.4Zr0.12 alloy.…”
Section: Methodssupporting
confidence: 60%